Statins impair glucose uptake in human cells. Issue 1 (29th April 2014) - Nowis, Dominika; Malenda, Agata; Furs, Karolina; Oleszczak, Bozenna; Sadowski, Radoslaw; Chlebowska, Justyna; Firczuk, Malgorzata; Bujnicki, Janusz M; Staruch, Adam D; Zagozdzon, Radoslaw; Glodkowska-Mrowka, Eliza; Szablewski, Leszek; et al.
Abstract : Objective: Considering the increasing number of clinical observations indicating hyperglycemic effects of statins, this study was designed to measure the influence of statins on the uptake of glucose analogs by human cells derived from liver, adipose tissue, and skeletal muscle. Design: Flow cytometry and scintillation counting were used to measure the uptake of fluorescently labeled or tritiated glucose analogs by differentiated visceral preadipocytes, skeletal muscle cells, skeletal muscle myoblasts, and contact-inhibited human hepatocellular carcinoma cells. A bioinformatics approach was used to predict the structure of human glucose transporter 1 (GLUT1) and to identify the presence of putative cholesterol-binding (cholesterol recognition/interaction amino acid consensus (CRAC)) motifs within this transporter. Mutagenesis of CRAC motifs in SLC2A1 gene and limited proteolysis of membrane GLUT1 were used to determine the molecular effects of statins. Results: Statins significantly inhibit the uptake of glucose analogs in all cell types. Similar effects are induced by methyl-β-cyclodextrin, which removes membrane cholesterol. Statin effects can be rescued by addition of mevalonic acid, or supplementation with exogenous cholesterol. Limited proteolysis of GLUT1 and mutagenesis of CRAC motifs revealed that statins induce conformational changes in GLUTs. Conclusions: Statins impair glucose uptake by cells involved in regulation of glucose homeostasis by inducing cholesterol-dependent conformational changes in GLUTs. This molecular mechanism might explain hyperglycemic effects of statins observed in clinical trials.